ENHANCING RECOVERY IN DIABETIC KETOACIDOSIS: THE ROLE OF BASAL INSULIN (GLARGINE) WITH INTRAVENOUS INSULIN INFUSION - Muhammad Wajahatullah; Inayat Ali Khan; Zeeshan Ali; Atiqa Alvi; Saiyida Kaunain Fatima; Mariyam Sikander (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Background: One of the most life threatening metabolic complication of diabetes mellitus (DM) and with a high mortality rate is diabetic ketoacidosis (DKA).Objectives: To evaluate the use of insulin glargine in addition to intravenous insulin infusion in treatment of DKA.Methods: This multi-centered prospective cross sectional analytical study was carried out at Department of Emergency of all three different campuses of Ziauddin University, Karachi for six months (January 2023 to June 2023) using non-probability consecutive sampling. The International Society for Pediatric and Adolescent Diabetes (ISPAD) Clinical Practice Consensus Guidelines 2018 were used for diagnosing DKA. Through simple random technique, patients were divided into group A (Insulin infusion only) and group B (Insulin + Insulin Glargine infusion). SPSS version 23.0 was used for analyzing data. Independent t-test was applied for the laboratory findings which were compared between group A and group B.Results: A total of 139 DKA patients (mean age 54.6 years, 61.9% female) were studied. At baseline, they presented with severe hyperglycemia, acidosis, and elevated anion gap. After 6 hours, both groups showed significant glucose reduction, with no difference between insulin infusion alone and insulin plus glargine. However, patients receiving glargine demonstrated faster metabolic recovery, reflected by higher bicarbonate, improved arterial pH, and lower anion gap. Renal function and osmolality improved similarly in both groups.Conclusion: Adding basal insulin (glargine) to standard intravenous insulin infusion accelerated the resolution of metabolic acidosis and improved biochemical recovery in DKA patients, without affecting glucose reduction or renal function.